Theoretical basis of the concept for technical service of machines on actual state based on assessed parametric reliability - D. V. Varnakov; O. N. Didmanidze (Аграрная наука Евро-Северо-Востока, 2017)
The basic approaches to modeling of technical service according to the actual state of the machine in order to optimize maintenance actions and cost reduction is examined in the article. Methods for evaluating the efficiency of machines functioning that allow to determine the quantitative characteristics of the parameters of its work during the operation, as well as to predict parametric reliability. One of the promising ways of increasing the efficiency of the service centers is the use of modern machinery diagnostic tools, namely continuous diagnostics. Based on the proposed method of assessing the effectiveness of the functioning of machines it was produced an assessment not only by the intrinsic properties of the most complex system, but taking into account the quality of its functioning, the quality of the task solving. Thus, maintenance of machinery condition can be characterized by an indication of defects, violation of their good working condition, as well as the quality of the operation, and refer to the details, nodes, or to the machine as a whole. Choosing the optimal strategy of technical service allows to achieve the best results due to the reorganization of the rules of operation without additional forces and resources. To solve the problem of a rational maintenance intervals a mathematical model was used that describes the evolution of the technical condition of the machine in time, taking into account the fluctuations of the parameters and random processes. Among technical service tasks it were onsidered indicators of quality of functioning of machines at continuous operation. To find the optimal strategy for such tasks it was proposed to use the minimax method. It was informed that the continuous monitoring of the parametric reliability of vehicles will optimize service intervals, as well as the use of technical methods of forecasting.Thus, the study of methods of increasing the reliability of equipment particularly important are tasks related to the assessment of its parametric reliability.